The Effect of the project-based E-learning strategy in reducing mind wandering for the female students of the third intermediate grade in Jeddah city - Alqahtani, Somaya Hamed; Alharthi, Majed Abdallah (Journal of Educational and Psychological Sciences, 2022)
The current study examined the effect of the project-based e-learning strategy on reducing the mind wandering that applied with third-grade intermediate students in Jeddah city. The study also aimed to identify the differences between the experimental and control groups in reducing the mind wandering in the study sample due to the use of the project-based e-learning strategy for the third intermediate grade students in Jeddah city. The study adopted the quasi-experimental approach, where the study sample consisted of (64) female students of the Third Intermediate Grade in Jeddah City. They were randomly distributed into (2) two groups, a control group (32) and an experimental group (32), The study used the mind wandering questionnaire a research tool, The results revealed that there were statistically significant differences at (α≤0.05) on the post-measurement between the averages of the experimental and control groups on the total degree in reducing mind wandering in favor of the experimental group. T test was (6.01), and the weighted average of the experimental group on the mind wandering questionnaire was (3.07), which is less than the weighted average of the control group, which amounted to (3.69), which indicates that the level of low level of mind wandering was better for the experimental group due to the use of the e-learning strategy project-based. Depend on of these results, the study recommended Training teachers on modern e-learning strategies, including the project-based e-learning strategy, educating them and encouraging them to apply it in teaching many courses, include e-projects in all curricula and issue ministry-wide awards to encourage innovation in classrooms.
Keywords: Project Based E-learning Strategy; Mind Wandering